Molecular epidemiology of carbapenemase-producing Klebsiella pneumoniae isolates obtained from community-acquired urinary tract infections and rectal carriage isolates - Kock, Marleen Magdalena (University of Pretoria, 2024)
Thesis (PhD (Medical Microbiology))--University of Pretoria, 2023.